An evaluation of the assessment tool used for extensive mini-dissertations in the Master’s Degree in Family Medicine, University of the Free State - H. Brits; J. Bezuidenhout; W.J. Steinberg; G. Joubert (South African Family Practice)
Background: Family Medicine became a speciality in South Africa in 2007. Postgraduate studies in Family Medicine changed from part-time Master of Family Medicine (MFamMed) to a full-time Master of Medicine (Family Medicine) [MMed(Fam)] degree, with changes in the curriculum and assessment criteria. The overall goal of this study was to evaluate the current assessment tool for extensive mini-dissertations in the postgraduate programme for Family Medicine, at the University of the Free State, and if necessary, to produce a valid and reliable assessment tool that is user-friendly.